2018
DOI: 10.1007/s00167-018-4856-z
|View full text |Cite
|
Sign up to set email alerts
|

Improved walking distance and range of motion predict patient satisfaction after TKA

Abstract: Purposes The focus in the evaluation of total knee arthroplasty has shifted from objective measures of implant position and knee function, to patient-reported outcome measures (PROMs). The relation between these two measures was investigated and the possibility of prediction of the patient satisfaction level was evaluated by defining thresholds for improvement of (1) range of motion (ROM), (2) 6-min walk test (6MWT), (3) sit-to-stand test (STS) and (4) quadriceps force after TKA? Methods Fifty-seven patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(39 citation statements)
references
References 39 publications
3
36
0
Order By: Relevance
“…Many participants expressed relief at the end of the interview when the researcher offered them an opportunity to receive more information and ask questions regarding their TKA. The therapeutic effect of qualitative interviews is also described in other patient groups [46][47][48].…”
Section: Discussionmentioning
confidence: 99%
“…Many participants expressed relief at the end of the interview when the researcher offered them an opportunity to receive more information and ask questions regarding their TKA. The therapeutic effect of qualitative interviews is also described in other patient groups [46][47][48].…”
Section: Discussionmentioning
confidence: 99%
“…The participants in our study described discontentment because they were not fully informed regarding the somewhat limited range of motion that could be expected postoperatively. A recent study showed that an improvement of five degrees in the range of motion in the knee after surgery along with an improved walking distance could increase the satisfaction rate by 6-8 times [49]. Other studies also agree with the effect of stiffness on satisfaction [50,51].…”
Section: Discussionmentioning
confidence: 69%
“…In the current study the patients' course of recovery was not investigated, only if there were complications or not. So it was not known whether these patients met the range of motion and walking distance improvements reported in the literature [49].…”
Section: Discussionmentioning
confidence: 92%
“…and tissue cultures [3,9,16]. The methods used to evaluate functional recovery include an early postoperative range of motion (ROM) measurement, a quadriceps muscle strength measurement, the sit to stand test, the 6-minute walking test [18], and a psychological assessment [7].…”
Section: Introductionmentioning
confidence: 99%